2010
DOI: 10.1111/j.2042-3306.2010.00033.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparisons of overground endoscopy and treadmill endoscopy in UK Thoroughbred racehorses

Abstract: Care should be taken in interpreting negative findings during both procedures, but particularly during overground endoscopy if racing conditions have not been appropriately replicated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(52 citation statements)
references
References 26 publications
3
47
0
Order By: Relevance
“…Horses presented for DOE may be more valuable horses, or horses with more severe diseases, and therefore this sample may not reflect the Thoroughbred racehorse population in South Africa as a whole. Whilst the mean maximal speed reported in the present study (58 km/h) is similar to the 56 km/h reported for 140 Thoroughbred racehorses undergoing DOE and is similar to the average racing speed of 58 km/h for the winning horse in flat races up to 1.6 km (1 mile) (Allen & Franklin 2010), horses that ran short distances or attained lower speeds during DOE may not have developed any detectable conditions or the actual performance-limiting condition that may have occurred during actual training or racing. …”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Horses presented for DOE may be more valuable horses, or horses with more severe diseases, and therefore this sample may not reflect the Thoroughbred racehorse population in South Africa as a whole. Whilst the mean maximal speed reported in the present study (58 km/h) is similar to the 56 km/h reported for 140 Thoroughbred racehorses undergoing DOE and is similar to the average racing speed of 58 km/h for the winning horse in flat races up to 1.6 km (1 mile) (Allen & Franklin 2010), horses that ran short distances or attained lower speeds during DOE may not have developed any detectable conditions or the actual performance-limiting condition that may have occurred during actual training or racing. …”
Section: Discussionsupporting
confidence: 87%
“…In the present study, abnormal arytenoid function at exercise was observed in 33% of horses evaluated for poor performance and/or respiratory noise. Dynamic endoscopy in similar populations has detected this in approximately 8% -40% of horses (Allen & Franklin 2010;Barakzai & Dixon 2011;Dart et al 2001;Desmaizieres et al 2009;Tan et al 2005). Dorsal displacement of the soft palate was also one of the most commonly detected abnormalities in the present study (25%) (Figure 7), similar to the proportion of horses reported with DDSP in comparative populations: 19% (Pollock et al 2009), 26% (Witte et al 2011) and28% (Desmaizieres et al 2009).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Although both modalities are widely accepted, a higher diagnostic rate of DDSP has been reported with high-speed treadmill endoscopy presumably because of failure of over-the-ground endoscopy to create the exertion of high-speed treadmill. 27 In contrast, there is strong evidence that head and neck position influences DDSP and therefore over-the-ground endoscopy, although being ridden under normal conditions including head and neck positioning, is more likely to result in an accurate diagnosis. 22 Therefore, the recommendation to achieve the most accurate diagnosis is to make every effort to recreate race or performance conditions including speed, duration, tack, and head and neck positions.…”
Section: Summary Of Etiopathogenesismentioning
confidence: 91%
“…[2][3][4][5] Variables such as lack of standardization of the exercise tests, shorter training distances, and an inability to re-create racing conditions have been proposed.…”
Section: Upper Airway Endoscopy During Exercisementioning
confidence: 99%